Conversor Buck: conversão de MATLAB para Scilab - Souza, Nirlan Neckir Zamprogno de; Custódio, Eliane Silva; Gonçalves, Maria Aline (Caderno Progressus, 2024)
O estudo propõe a conversão de um modelo de conversor Buck que foi originalmente desenvolvido em MATLAB/Simulink, para o ambiente Scilab/Xcos. Essa conversão visa oferecer uma alternativa gratuita para modelagem e simulação em eletrônica de potência. Tanto o MATLAB quanto o Scilab possuem operadores e funções fundamentais em comum. A principal diferença entre os dois softwares está nas funções específicas para a criação e manipulação de funções de transferência. Esse estudo também explora a conversão de blocos específicos do Simulink para o Xcos. Nesse trabalho, são obtidas com sucesso as funções de transferência, os diagramas de Bode e a resposta a um trem de impulsos. Apesar do Scilab ter uma documentação menor, menos didática e com menos exemplos de aplicação do que o MATLAB, o presente estudo demonstrou que é perfeitamente possível converter uma modelagem realizada em MATLAB e Simulink para Scilab e Xcos e obter quase todas as informações do modelo. Palavras-chave: conversor Buck; MATLAB; Scilab; função de transferência; discretização. Abstract The study proposes the conversion of a buck converter model, originally developed in MATLAB/Simulink, to the Scilab/Xcos environment. The objective of this conversion is to provide a cost-free alternative for modeling and simulation in the field of power electronics. Both MATLAB and Scilab are based on a similar set of fundamental operators and functions. The primary distinction between the two software platforms pertains to the specific functions for creating and manipulating transfer functions. Furthermore, this study examines the conversion of Simulink blocks to Xcos. In this process, transfer functions, bode diagrams, and impulse train responses have been successfully obtained. Despite Scilab having less comprehensive documentation, a less didactic approach, and a smaller selection of application examples in comparison to MATLAB, the present study has demonstrated that it is feasible to convert a model developed in MATLAB and Simulink to Scilab and Xcos, and to retrieve most of the information from the model. Keywords: Buck converter; MATLAB; Scilab; transfer function; discretization. Resumen El estudio propone la conversión de un modelo de convertidor Buck, originalmente desarrollado en MATLAB/Simulink, para el Scilab/Xcos. Esa conversión tiene como objetivo ofrecer una alternativa gratuita para la modelización y simulación en electrónica de potencia. Tanto MATLAB como Scilab comparten operadores y funciones fundamentales. La principal diferencia entre los dos programas radica en las funciones específicas para la creación y manipulación de funciones de transferencia. Ese estudio también explora la conversión de bloques específicos de Simulink a Xcos. En ese trabajo se obtienen con éxito las funciones de transferencia, los diagramas de Bode y la respuesta a un tren de impulsos. A pesar de que Scilab tiene menos documentación, es menos didáctico y ofrece menos ejemplos de aplicación en comparación con MATLAB, el presente estudio demostró que es perfectamente posible convertir una modelización realizada en MATLAB y Simulink a Scilab y Xcos y obtener casi toda la información del modelo. Palabras clave: Convertidor Buck; MATLAB; Scilab; función de transferencia; discretización.